Therapeutic Jurisprudence and Restorative Justice in Brazil - Traguetto, Jessica (International journal of offender therapy and comparative criminology, 2020)
The Brazilian prison population in 2016 had increased by more than 700%, compared with the situation in the early 1990s, from 90 thousand to 726.7 thousand. The ordinary response to prison overcrowding came through changes to the justice system, such as Therapeutic Jurisprudence and Restorative Justice. Although these new processes are socially relevant, there are few studies about them anywhere, but especially in Brazil. This study seeks to discuss the perceptions of Brazilian judges upon these new ways of dispensing justice from the perspective of institutional change theory. The data collection involved document analysis, court-hearing observations, and interviews with 14 key-actors in the Brazilian justice system. The results show four dimensions—beliefs, motivations, commitment, and intergroup relations—that characterize the roles played by Brazilian judges working with Therapeutic Jurisprudence and Restorative Justice. This movement can be classified as the modal type of institutional change called layering and "radical" frame blending.